Cost, revenue, and profit efficiency of Islamic versus conventional banks: international evidence using data envelopment analysis - Shamsher, Mohamad; Bader, Mohammed Khaled I.; Hassan, Taufiq; Ariff, Mohamed (2008)
This paper measures and compares the cost, revenue, and profit efficiency of 43 Islamic and 37 conventional banks over the period 1990-2005 in 21 countries using Data Envelopment Analysis. In addition, it assesses the efficiency of those banks based on their size, age, and region. The findings suggest that there are no significant differences between the overall efficiency results of conventional versus Islamic banks. However, there is substantial room for improvement in cost minimisation and revenue and profit maximisation in both banking systems. Furthermore, the findings show no significance difference in average efficiency scores between big versus small and new versus old banks in both banking streams. This implies that size and age did not affect the performance of banks in both streams. However, geographical location explains the significant differences in revenue and profit efficiency between both streams of banks. Overall, the results are in favour of the more recent Islamic banking system.